2021
DOI: 10.1021/acs.orglett.1c02981
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Triggered Sulfonylation/Aryl Migration/Desulfonylation and C–S/Se Bond Formation Reaction: 1,2,4-Trifunctionalization of Butenyl Benzothiazole Sulfone with Thiosulfonate/Selenosulfonates

Abstract: A visible-light-triggered radical cascade sulfonylation/aryl migration/desulfonylation and C–S/Se bond formation reaction of butenyl benzothiazole sulfone with thiosulfonates or selenosulfonates is developed. This study affords the 1,2,4-trifunctionalization of butenyl benzothiazole sulfone derivatives under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…We first synthesized compound 1a, same as before, 7 which did not occur under standard reaction conditions ( of 78%. Then, we experimented with the effect of different solvents on the reaction and found that the reaction was still the best in DMF.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We first synthesized compound 1a, same as before, 7 which did not occur under standard reaction conditions ( of 78%. Then, we experimented with the effect of different solvents on the reaction and found that the reaction was still the best in DMF.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We then carried the resulting β‐sulfonyl alkyl heteroarenes for a series of synthetic manipulations. Products 4 and 18 underwent facile β‐sulfone elimination in the presence of strong bases to afford α‐heteroaryl dihydrofurans 41 and 42 in 95 % yields [15] . Catalytic hydrogenation of dihydrofuran 42 with H 2 in the presence of Pd/C gave α‐heteroaryl tetrahydrofuran 43 in 91 % yield [16] .…”
Section: Resultsmentioning
confidence: 99%
“…Thio- and selenosulfonate (PhS–SO 2 Ph and PhSe–SO 2 Ph) are reported to capture carbon radicals, and excellent examples using PhS–SO 2 Ph for the introduction of sulfur-centered functional groups into several building blocks are shown in Scheme 5 . In the presence of radical initiators or under light, the corresponding sulfur-centered radicals are generated from PhS–SO 2 Ph, and sequential radical cascade reactions driven by trapping carbon radicals with them provide pharmaceutical and functional molecule scaffolds in one pot [ 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: The Group 16 Element (O S Se and Te)-centered Interelement C...mentioning
confidence: 99%